Radiosurgery in Treatment of Ventricular Tachycardia – Initial Experience Within the Polish SMART-VT Trial - Kurzelowski, Radosław; Latusek, Tomasz; Miszczyk, Marcin; Jadczyk, Tomasz; Bednarek, Jacek; Sajdok, Mateusz; Gołba, Krzysztof S.; Wojakowski, Wojciech; Wita, Krystian; Gardas, Rafał; Dolla, Łukasz; Bekman, Adam; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Stereotactic Arrhythmia Radioablation (STAR) is an emerging treatment modality for patients with sustained ventricular tachycardia (VT) and refractory to treatment with drugs and radiofrequency catheter ablation (RFA). It is believed that up to 12-17% of patients experience recurrence of VT within one year of follow-up; thus, novel therapeutic options are needed. The aim of this article is to present initial experience within a novel treatment modality for VT. Case summary: Two patients with a medical history of coronary artery disease and heart failure with reduced left ventricle (LV) ejection fraction, after implantation of cardioverter-defibrillator (ICD) and previous unsuccessful RFAs owing to sustained VT were admitted to the cardiology department due to recurrence of sustained VT episodes. With electroanatomical mapping (EAM), the VT substrate in LV has been confirmed and specified. In order to determine the target volume for radioablation, contrast-enhanced computed tomography was performed and the arrhythmia substrate was contoured using EAM data. Using the Volumetric Modulated Arc Therapy technique and three 6 MeV flattening filter-free photon beam fields, a single dose of 25 Gy was delivered to the target volume structure located in the apex and anterior apical segments of LV in the first patient and in the apex, anterolateral and inferior apical segments of the second patient. In both cases, volumes of the target structures were comparable. Interrogation of the implanted ICD at follow-up visits throughout 6 months after the treatment revealed no VT episodes in the first patient and sudden periprocedural increase in VT burden with a subsequent gradual decrease of ventricular arrhythmia to only two non-sustained episodes at the end of the follow-up period in case of the second patient. A significant reduction in premature ventricular contractions burden was observed compared to the pre-treatment period. No noticeable deterioration in LV function was noted, nor any adverse effects of radiosurgery associated with the implanted device. Conclusion: The early response to STAR can be unpredictable and probably does not reflect the final outcome of irradiation. Close monitoring of patients, especially in the early period after irradiation is crucial to properly handle potentially harmful early reactions to STAR.